2019
DOI: 10.1101/730960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mechanical memory of pancreatic cancer cells

Abstract: Cells sense and respond to mechanical stimuli in healthy and pathological conditions. Although the major mechanisms underlying cellular mechanotransduction have been described, it remains largely unclear how cells store information on past mechanical cues over time. Such mechanical memory is extremely relevant in the onset of metastasis in which cancer cells migrate through tissues of different stiffness, e.g. from a stiffer tumor microenvironment to softer metastatic sites as commonly occurs for pancreatic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These are all genes involved in cell migr ECM adhesion, ECM remodeling, anti-apoptotic mechanisms an At this step, cells show less protein designated to maintain cell E-cadherin, causing a loss of tissue polarity, while they incre mentin, which is a marker of mesenchymal cells [68,121]. YAP/T can be similarly induced by the interaction of laminin 5 to α6β4 to maintain their stemness, as shown in epidermal stem cells [12 EMT is triggered by the accumulation of YAP and the transcriptional coactivator with the PDZ-binding motif, also known as WWTR1 (TAZ), within the nuclei [119][120][121][122][123]. YAP and TAZ need DNA-binding partners, as YAP and TAZ have no DNA binding ability.…”
Section: Cellular Response To Stiffness and Solid Stressmentioning
confidence: 99%
“…These are all genes involved in cell migr ECM adhesion, ECM remodeling, anti-apoptotic mechanisms an At this step, cells show less protein designated to maintain cell E-cadherin, causing a loss of tissue polarity, while they incre mentin, which is a marker of mesenchymal cells [68,121]. YAP/T can be similarly induced by the interaction of laminin 5 to α6β4 to maintain their stemness, as shown in epidermal stem cells [12 EMT is triggered by the accumulation of YAP and the transcriptional coactivator with the PDZ-binding motif, also known as WWTR1 (TAZ), within the nuclei [119][120][121][122][123]. YAP and TAZ need DNA-binding partners, as YAP and TAZ have no DNA binding ability.…”
Section: Cellular Response To Stiffness and Solid Stressmentioning
confidence: 99%
“…Metastatic niche in a softer environment presents a higher intrinsic resistance to gemcitabine monotherapy, a standard first-line treatment for patients with metastatic pancreatic cancer. 393,394 In pancreatic cancer, YAP nuclear translocation and miR-21 expression mediate the mechanical memory in response to altered environmental stiffness. 393 Meanwhile, environmental stiffness can influence the gemcitabine chemoresistance of soft-primed pancreatic cancer cells.…”
Section: Molecular Mechanism Of the Crosstalk Between Mirnas And Yapmentioning
confidence: 99%
“…393,394 In pancreatic cancer, YAP nuclear translocation and miR-21 expression mediate the mechanical memory in response to altered environmental stiffness. 393 Meanwhile, environmental stiffness can influence the gemcitabine chemoresistance of soft-primed pancreatic cancer cells. These findings could shed light on how the regulation of miRNA expression affects tumor metastasis in patients, while miR-21 serve as a potential therapeutic target in metastatic tumor cells.…”
Section: Molecular Mechanism Of the Crosstalk Between Mirnas And Yapmentioning
confidence: 99%
“…Changes in stiffness at the invasive front of a tumour can trigger epithelial‐to‐mesenchymal transition (EMT) and, thus, modifications in the cancer cell cytoskeleton . Several in vitro studies have shown that cancer cells can acquire so‐called mechanical memory on a stiff substrate by activating yes‐associated protein‐1 (YAP) signalling, leading to persistently higher actomyosin expression . Later, after reaching a softer 2D substrate, these cells exhibit larger‐than‐normal focal adhesions and increased migration speed .…”
Section: Ecm As a Gatekeeper In Cancer Initiation And Progressionmentioning
confidence: 99%